2003
DOI: 10.1182/blood.v101.4.1558
|View full text |Cite
|
Sign up to set email alerts
|

Global down-regulation of HOX gene expression in PML-RARα+ acute promyelocytic leukemia identified by small-array real-time PCR

Abstract: IntroductionAcute promyelocytic leukemia (APL) is a subgroup of acute myelogenous leukemia (AML) typified by the t(15;17) leading to fusion of the putative growth suppressor PML to the retinoic acid receptor ␣ (RAR␣), which has been implicated in normal myelopoiesis. 1 Recent studies suggest that PML-RAR␣, which retains the ligand (RA)-binding domain and functions as an aberrant retinoid receptor at physiological levels of RA, leads to repression of downstream target genes (reviewed by Lin et al 2 ). This is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 55 publications
7
38
0
1
Order By: Relevance
“…23 A comparison of our results with previous reports of genomic profiling in AML is difficult because the majority of the studies are based on the cumulative analysis of different FAB subtypes and/or experimental systems are not fully comparable. [23][24][25][26][28][29][30] For example, the only report of expression profiling using normal promyelocytes is based on a mouse model of APL. 29 Interestingly, Valk et al 25 determined the gene expression profiles in samples from 285 patients with AML, including 19 APL cases, and normal bone marrow and CD34 þ samples derived from healthy control subjects and identified 16 groups of AML on the basis of molecular signatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 A comparison of our results with previous reports of genomic profiling in AML is difficult because the majority of the studies are based on the cumulative analysis of different FAB subtypes and/or experimental systems are not fully comparable. [23][24][25][26][28][29][30] For example, the only report of expression profiling using normal promyelocytes is based on a mouse model of APL. 29 Interestingly, Valk et al 25 determined the gene expression profiles in samples from 285 patients with AML, including 19 APL cases, and normal bone marrow and CD34 þ samples derived from healthy control subjects and identified 16 groups of AML on the basis of molecular signatures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed clear downmodulation of HOX gene expression in line with a previous report. 30 The functional analysis of the supervised approach results (1020 transcripts), that is, the genes modulated in leukemic versus normal promyelocytes revealed that PML-RARA influences the expression of genes involved in the control of different cellular functions, including lipid metabolism, DNA repair and cell cycle. Interestingly, a trend toward a transcriptional repression of genes involved in diverse mechanisms of DNA repair and cell cycle control was found in leukemic promyelocytes.…”
Section: Discussionmentioning
confidence: 99%
“…(C (a and b)) Global overview of normalized expression of all class I HOX genes tested in inv(7) positive T-ALLs (cases no. [15][16][17][18][19], inv(7) negative T-ALLs (cases no. 2-11 and no.…”
Section: Discussionmentioning
confidence: 99%
“…Total BM was collected by flushing femurs and tibias of agematched control or A9M-L2 mice, and total RNA was isolated and cDNAs were generated as previously described [30]. For stem cell pluripotency and immune response profiling, cDNA samples were prepared with TaqMan Universal PCR mix and (200 ng/100 lL) loaded into each of the eight ports on the predesigned 384 well cards of the TaqMan Gene Expression Array.…”
Section: Gene Expression Profilingmentioning
confidence: 99%